Answer:
Thus, the answer is:
Explanation:
Considering the system of equations
Rewrite the system in matrix form and solve it by Gaussian Elimination (Gauss-Jordan elimination)
R2 - 4 R1 → R2 (multiply 1 row by 4 and subtract it from 2 row); R3 - 1 R1 → R3 (multiply 1 row by 1 and subtract it from 3 row)
R2 / -3 → R2 (divide the 2 row by -3)
R1 - 1 R2 → R1 (multiply 2 row by 1 and subtract it from 1 row); R3 + 2 R2 → R3 (multiply 2 row by 2 and add it to 3 row)
R3 / 5 → R3 (divide the 3 row by 5)
R2 - 1 R3 → R2 (multiply 3 row by 1 and subtract it from 2 row)
Thus, the answer is:
Make a check:
4 + 2 + (-4) = 4 + 2 - 4 = 2
4·4 + 2 + (-4) = 16 + 2 - 4 = 14
4 - 2 + 4·(-4) = 4 - 2 - 16 = -14
Check completed successfully.